Intestinal Absorption of Bile Acids in Health and Disease - Ticho, Alexander L; Malhotra, Pooja; Dudeja, Pradeep K; Gill, Ravinder K; Alrefai, Waddah A (Comprehensive Physiology, 2019)
The intestinal reclamation of bile acids is crucial for the maintenance of their enterohepatic circulation. The majority of bile acids are actively absorbed via specific transport proteins that are highly expressed in the distal ileum. The uptake of bile acids by intestinal epithelial cells modulates the activation of cytosolic and membrane receptors such as the farnesoid X receptor (FXR) and G protein-coupled bile acid receptor 1 (GPBAR1), which has a profound effect on hepatic synthesis of bile acids as well as glucose and lipid metabolism. Extensive research has focused on delineating the processes of bile acid absorption and determining the contribution of dysregulated ileal signaling in the development of intestinal and hepatic disorders. For example, a decrease in the levels of the bile acid-induced ileal hormone FGF15/19 is implicated in bile acid-induced diarrhea (BAD). Conversely, the increase in bile acid absorption with subsequent overload of bile acids could be involved in the pathophysiology of liver and metabolic disorders such as fatty liver diseases and type 2 diabetes mellitus. This review article will attempt to provide a comprehensive overview of the mechanisms involved in the intestinal handling of bile acids, the pathological implications of disrupted intestinal bile acid homeostasis, and the potential therapeutic targets for the treatment of bile acid-related disorders. Published 2020. Compr Physiol 10:21-56, 2020.